What are the most frequent diagnoses in adolescence? The reality of an Adolescent Medicine Clinic - Abreu,Nina (2018)
ABSTRACT Objective To characterize the care flow and the primary diagnoses of an Adolescent Medicine Clinic. Methods A retrospective descriptive study, with analysis of clinical processes of adolescents (10-18 years) seen at the Adolescent Medicine Clinic, from January 2006 to December 2013. The following variables were analyzed: sex, age, number of visits, referring service and primary diagnoses according to the International Statistical Classification of Diseases and Related Health Problems. As to the variable age, the adolescents were divided into two groups: Group I comprised those aged 10-14 years, and Group II, 15-18 years. Results A total of 7,692 visits were carried out, in that, 1,659 first visits (22%), with an annual growth rate of 6%. The mean age was 14.2 years, and 55% of patients were female. The group of endocrine, nutritional and metabolic diseases was the most representative in our sample (34%), with obesity being the most frequent diagnosis in both sexes and age groups (23%), with a higher prevalence in males (13% male versus 10% female, p<0.001) and younger adolescents (18% in Group I versus 5% in Group II p<0.001). The group of mental and behavioral disorders was the second most prevalent (32%), affecting mainly females (39% female versus 22% male, p<0.001) and the older age group (39% Group II versus 27% Group I, p<0.001). Social problems were the primary diagnosis in 8% of visits. Conclusion Most diseases diagnosed have a strong behavioral and social component, particularly mental disorders and obesity. This specific type of diagnoses reinforces the need for a global approach for adolescents and specialized adolescent medicine units/clinics.